Tumor venéreo transmissível com metástases cutâneas em um cão transmissible venereal - Moutinho, Flavio Quaresma [UNESP]; Sampaio, Gabriela Rodrigues [UNESP]; Teixeira, Carlos Roberto [UNESP]; Sequeira, Julio Lopes [UNESP]; Amorim, Renée Laufer [UNESP] (Universidade Federal de Santa Maria (UFSM), 1995)
O tumor venéreo transmissível é diagnosticado, na maioria das vezes, em animais jovens, sadios e sexualmente ativos. Acomete, comumente, a genitália externa. Metástases, apesar de incomuns, ocorrem. O presente trabalho relata um caso de tumor venéreo transmissível na glande peniana com disseminação para a pele das regiões abdominal e inguinal.

Transmissible venereal tumor is most of the times diagnosed in young, healthy and sexually active animais. In general it affects any part of external genitalis; metastasis, although uncommon, may occur. This paper reports a case of a transmissible venereal tumor, in the glans penis of a dog with spread to the skin of abdominal and inguinal regions.
Tumor with cutaneous metastasis in a dog
Keywords: Tumor venéreo transmissível; cão; metástase; Transmissible venereal tumor; dog diseases; tumor metastasis